Artificial intelligence for capital markets - Jafar, Syed Hasan (Boca Raton : Chapman & Hall/CRC Press, 2023)
"Artificial Intelligence for Capital Market throws light on application of AI/ML techniques in the financial capital markets. This book discusses the challenges posed by the AI/ML techniques as these are prone to "black box" syndrome. The complexity of understanding the underlying dynamics for results generated by these methods is one of the major concerns which is highlighted in this book"--
OCLC-licensed vendor bibliographic record.
Keywords: Capital market; Artificial intelligence; Machine learning; COMPUTERS / Computer Science; COMPUTERS / Neural Networks